2018
DOI: 10.4194/1303-2712-v18_1_04
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Three major carps namely; Labeo rohita, Catla catla, Cirrhinus mrigala are commercially important aquaculture freshwater fish species of Pakistan. Ascertaining the pure species status of major carps is essential for their appropriate management and conservation. The use of microsatellites DNA markers and Bayesian models based statistical methods have considerably improved the estimation of admixture analyses at individual level. In the present study, a set of twelve heterologus microsatellite markers were empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Genetic studies have recently shown that heterologous microsatellite markers are able to differentiate hybrid species from pure species as assessed by Parveen, Abbas, Afzal & Hussain (2018) in a study with three species of carp (Labeo rohita, Catla catla, and Cirrhinus mrigala) and Esquer-Garrigos et al (2015) in Andean pupfishes (Orestias agassizii and O. luteus). This is very important when dealing with species of the Pimelodidae family, since the intergenic hybridization of catfish, including L. marmoratus and P. reticulatum, is common in South American fish farms (Hashimoto, Prado, Foresti & Porto-Foresti, 2016), and may present risks of genetic contamination of natural stocks by accidental releases, leading to genetic introgression (Hashimoto, Senhorini, Foresti, Martínez, & Porto-Foresti, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic studies have recently shown that heterologous microsatellite markers are able to differentiate hybrid species from pure species as assessed by Parveen, Abbas, Afzal & Hussain (2018) in a study with three species of carp (Labeo rohita, Catla catla, and Cirrhinus mrigala) and Esquer-Garrigos et al (2015) in Andean pupfishes (Orestias agassizii and O. luteus). This is very important when dealing with species of the Pimelodidae family, since the intergenic hybridization of catfish, including L. marmoratus and P. reticulatum, is common in South American fish farms (Hashimoto, Prado, Foresti & Porto-Foresti, 2016), and may present risks of genetic contamination of natural stocks by accidental releases, leading to genetic introgression (Hashimoto, Senhorini, Foresti, Martínez, & Porto-Foresti, 2014).…”
Section: Resultsmentioning
confidence: 99%